Atos discursivos interativos nas variedades do português falado - Fontes, Michel Gustavo [UNESP]; Pezatti, Erotilde Goreti [UNESP] (My University, 2011)
This paper aims to analyze and to characterize the structure of some linguistic expressions that, in the view of Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008), are called Interactive Acts because they show the Speaker, the Addressee and the Illocution positions filled in. To do so, we analyse data composed of representative texts of Portuguese spoken in Portugal, in Brazil, in African countries (those that have Portuguese as official language) and in East Timor

Este artigo objetiva analisar e caracterizar, no português falado, as estruturas linguísticas que, do ponto de vista da Gramática Discursivo-Funcional (HENGEVELD; MACKENZIE, 2008), denominam-se Atos Discursivos Interativos, já que têm preenchidas as posições para Ilocução, Falante e Destinatário. Para tanto, utilizam-se, como material de análise, textos representativos da língua portuguesa falada em Portugal, no Brasil, nos países africanos de língua oficial portuguesa e no Timor Leste.
Interactive discourse acts in spoken Portuguese varieties
Keywords: gramática discursivo-funcional; nível interpessoal; atos discursivos interativos; marcadores discursivos; functional discourse grammar; interpersonal level; interactive discourse acts; discourse markers